1999
DOI: 10.1063/1.478462
|View full text |Cite
|
Sign up to set email alerts
|

The rotational and vibrational dynamics of argon–methane. I. A theoretical study

Abstract: Reported here is a theoretical calculation of the spectrum of the argon-methane complex based upon a previously reported ab initio potential energy surface ͓T. G. A. Heijmen et al., J. Chem. Phys. 107, 902 ͑1997͔͒. The irregular rotational structure observed in the spectrum is traced to a combination of the fact that the excited vibrational state of the methane has vibrational angular momentum and the methane rotates nearly freely within the complex. The theoretical spectrum is compared qualitatively with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…6 For very simple gaseous systems it is even possible to calculate the thermal diffusion coefficient by ab initio methods. 7,8 In gas mixtures, where the interactions between molecules are dominated by hard sphere repulsion, it is predicted and experimentally observed that the heavier component migrates to the cold side ͑positive S T ). 6 Analogous results are also typically observed for liquid mixtures, such as polymer solutions and colloidal suspensions, where the solute is much heavier than the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…6 For very simple gaseous systems it is even possible to calculate the thermal diffusion coefficient by ab initio methods. 7,8 In gas mixtures, where the interactions between molecules are dominated by hard sphere repulsion, it is predicted and experimentally observed that the heavier component migrates to the cold side ͑positive S T ). 6 Analogous results are also typically observed for liquid mixtures, such as polymer solutions and colloidal suspensions, where the solute is much heavier than the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…10 for the rationale of this so-called asymptotic scaling technique. In our earlier work on the infrared spectrum of the argon-methane system 28,29 we found that this scaling technique led to good results.…”
Section: ͑13͒mentioning
confidence: 93%
“…The experimental infrared spectrum of methane-Ar was first presented at the 1994 Faraday Discussion on van der Waals molecules, without an assignment or interpretation, however. [25][26][27] Later it was demonstrated 28,29 that this spectrum can be understood and assigned by means of ab initio calculations. The different bands observed in the infrared spectrum correspond to excitation of the asymmetric C-H stretch ( 3 ) vibrational mode of methane, in combination with several intermolecular vibrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some information can also be obtained by comparing the experimental and theoretical differential cross sections, but here the experimental data are usually not state-resolved, and thus are less sensitive to the fine details of the potential. It has been already demonstrated in the 1990s that the ab initio potentials for simple atom-molecule systems like He-CO (Heijmen et al 1997b) or Ar-CH 4 (Heijmen et al 1999b;Miller et al 1999) reproduce the experimental high-resolution spectra very well. For some other systems, such Ne-CO (Moszynski et al 1997) or Ne-C 2 H 2 (Bemish et al 1998), small scalings were necessary to quantitatively reproduce the experimental data.…”
Section: Methodologies For Collisions With Heavy Particlesmentioning
confidence: 99%